2021
DOI: 10.1186/s12888-021-03205-2
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Prevalence of depression and associated factors among elderly people in Womberma District, north-west, Ethiopia

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
4
1
0
Order By: Relevance
“…In our study, being female was a statistically significant factor predisposing to the onset of a depressive episode. A similar finding has been noted in previous studies carried out in Kerala [7,[9][10][11], other Indian states [25,15], and other countries [26][27][28][29][30]. Such findings could be attributed to the genetic predisposition, varying coping styles, and the existing perceptions about a woman's role in a family and society.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, being female was a statistically significant factor predisposing to the onset of a depressive episode. A similar finding has been noted in previous studies carried out in Kerala [7,[9][10][11], other Indian states [25,15], and other countries [26][27][28][29][30]. Such findings could be attributed to the genetic predisposition, varying coping styles, and the existing perceptions about a woman's role in a family and society.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, older individuals with these comorbidities were found to be more prone to depressive episodes, as has been robustly recorded in the available literature [6,9,12,13,21,25,28,31]. Elderly individuals who were staying alone, and those who were widowed, were noted to be more depressed, a finding which has been amply recorded in the existing literature.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding the prevalence of depression, the finding of the current study is in line with studies conducted in Nepal, 53.1% (37); South Africa, 51.9% (38); and North Shoa, 54.6% (15). The finding of this study is higher when compared to studies conducted in Harar, 28.5% (13); Ambo, 41.8% (39); Dega Damot, 45.9% (13); Wenberema, 45% (17); Ghana, 37.8% (40); Egypt, 44.4% (16); and Morocco, 39.9% (41). Possible reasons for the discrepancies in these results might be differences in socio-demographic characteristics, sample sizes, and measurement scales used.…”
Section: Discussionsupporting
confidence: 88%
“…This could raise the likelihood of elderly people experiencing depression. This is also supported by studies conducted in Morocco (41) and Wemberema (17).…”
Section: Discussionsupporting
confidence: 74%
“…According to a meta‐analysis by Zenebe et al, 25 a high global prevalence of depressive symptoms was found among the older population ranging from 7.7% to 81.1%. Multiple factors are associated with geriatric depressive symptoms, such as being female, 26 older age, 27 being single or divorced, 28 lower educational attainment, unemployment, low income, 29 low self‐esteem, 30 loneliness or living alone, 31 social deprivation, 32 presence of chronic illness or poor health status, 33 lack of health insurance, 34 smoking habit, 35 cognitive impairment and a history of depressive symptom 25 . Despite geriatric depressive symptoms being a major problem, they are often undiagnosed, underdiagnosed, undertreated or diagnosed late 36 .…”
Section: Introductionmentioning
confidence: 99%